Muhadarah dan Eskalasi Kecerdasan Linguistik - Finy Fitriani (Study Program of Arabic Language Teaching, 2020)
The purpose of this study was to (1) describe the implementation of Muhadarah student activities in grade VI Islamic Arrisalah Slahung Ponorogo school year 2018/2019, (2) describe the linguistic intelligence of class VI Islamic Arrisalah Slahung Ponorogo students in 2018/2019 academic year in muhadarah activities.This type of research uses field research with a qualitative approach methodology. The study was conducted in grade VI of Arrisalah Slahung Ponorogo Islamic Elementary School with data collection procedures through observation, interviews, and documentation. The main data in the form of the contents of the video of the student Muhadarah that has been transcribed along with photos of the activities of the Muhadarah implementation. The subjects of the study were grade VI students and Arrisalah Islamic elementary school teachers. While the object of research is the linguistic intelligence of female students in grade VI Islamic elementary school Arrisalah Slahung Ponorogo. In this study the informants were the staff of the Arrisalah Islamic Elementary School teacher and the sixth grade guardian of Islamic Arrisalah Elementary School. Based on the results of data analysis, it can be concluded that (1) The implementation of muhadarah begins with the preparation of the text first, then corrects it to the supervisor. After completing the muhadarah activity, the supervisor evaluates and comments related to the performance displayed by the students, then continues by appointing several students who will be on duty for the following week. The assessment results for the six students who have performed the best speech are in the vocabulary and material aspects, with the average score is 4 to 5. While in other aspects there are still those who get a score of 3. (2) Language skills in the speaking aspects of the sixth grade students at SD Islam Arrisalah Slahung Ponorogo, the majority are good, can decipher and arrange words into effective sentence. With the existence of muḥā kegarah excitement held at this school can increase and improve linguistic intelligence/ language skills in aspects of their speech to be even better. The muhadarah activity is not only to improve language skills in speaking but also in writing, because before the children deliver their speeches in front of their class they first write the text and then memorize it.